Peran religiusitas dalam pembentukan konsep diri remaja - Muchtar, Desi Yustari (Fakultas Psikologi UIN Syarif Hidayatullah Jakarta, 2015)
This research wanted to know the effect of religiousity towards teenagers self-concept. Factor analysis of religiousity as predictor of teenagers self-concept was important to see the development of education process in order build the character of nation. It’s known that individual who have a positive self-concept always optimist, do new things, to success, not afraid to fail, have self-efficacy, enthusiastic, make a purpose of life, thinking positive, and become a leader that people can rely on. One factor that’s very important in self-concept is religion. Experience in religion that obtained by individuals since child can effected their personality when become an adult and be a part of their self-concept. This experience is called religiousity. This research involved 514 junior high school students in Tangerang Selatan. Result showed religiousity gave a significant effect toward teenagers self-concept by 24,7% (daily experience (14,9%); forgiving (3,9%); private practice (4,7%); religion as coping (0,7%)) DOI: 10.15408/tazkiya.v20i2.9165